The role of co-branding in brand loyalty - Minkkinen, Tiina (2024)
The relatively recent phenomenon of co-branding has attracted the attention of both researchers and brand managers due to the possibility of exploiting synergies between brands and achieving competitive advantage. In turn, the value of brand loyalty has been long recognized as it enables companies to establish long-term relationships with customers. However, the linkage between co-branding and brand loyalty remains under-studied and particularly the customer viewpoint seems to be overlooked. The main objective of this study was to increase the understanding on what meanings co-branding has for customers in building and preserving their brand loyalty. Secondly, this study aimed to identify co-branding elements that are important for customers’ loyalty. The third key objective was to discover how co-branding can strengthen or weaken the loyalty of customers. The empirical research was conducted between March and April, 2024 focusing on a genuine co-branding alliance between Marimekko and Adidas. A qualitative approach with semi-structured interviews were chosen as method to gain profound insights on the topic from the ten participants. To analyze the findings, thematic analysis and an inductive approach were applied to capture the participants’ experiences and meanings regarding the phenomenon. The findings of this research indicated that the meanings of co-branding, as well as customers' perceptions towards the brands and the brand alliance, can reflect on both attitudinal and behavioral loyalty. Furthermore, co-branding can lead to recommendations and prevent brand switching. Important co-branding elements for customers' loyalty were observed to revolve around the launch of cooperation, compatibility of the brands, brand backgrounds, availability, and other alliances. Co-branding experience, added value, and repetition and reach were identified as elements that can strengthen or weaken brand loyalty. This study contributes to the academic discussion through supporting extant knowledge and displaying novel observations to the phenomenon. The qualitative research approach helps deepen the understanding and expressing customers voice on the topic. Additionally, managerial implications and suggestions for further research pave way for future practices and discoveries.